Heat treatment method for improving creep property of LPBF nickel-based superalloy and nickel-based superalloy obtained through heat treatment method
By introducing a heat treatment method of sawtooth grain boundaries into the LPBF-formed nickel-based high-temperature alloy, the problem of low creep performance is solved, which significantly improves the high-temperature creep performance and maintains the room temperature mechanical properties.
Patent Information
- Application Number
- CN202510071351.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The nickel-based high-temperature alloy formed by LPBF is significantly lower than the forging level in terms of creep performance, mainly due to its unique microstructure characteristics, the stress concentration at the grain boundary, which increases the invasion and expansion rate of grain boundary cracks.
A heat treatment method is adopted, including homogenizing heat treatment, solution treatment and dual-stage aging heat treatment, introducing sawtooth grain boundaries to improve the microstructure of the material by changing the intermediate solution temperature and controlling the cooling speed.
By introducing serrated grain boundaries, the high-temperature creep performance of LPBF-formed nickel-based high-temperature alloy is significantly improved, while maintaining its room temperature mechanical properties, broadening its application range.
Smart Images

Figure CN119876807A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of nickel-based high-temperature alloys and heat treatment thereof, and in particular to a heat treatment method for improving the creep properties of LPBF nickel-based high-temperature alloys, and the nickel-based high-temperature alloys prepared by the method. Background Art
[0002] Nickel-based superalloys (such as Inconel 718) are typical precipitation-strengthened superalloys. They are widely used in hot-end components in the aerospace field because of their excellent strength, creep resistance and fatigue resistance below 650°C. As the demand for high performance and complexity of aerospace equipment accelerates, Inconel 718 superalloy faces significant challenges in the integrated manufacturing of precision and complex components.
[0003] Additive manufacturing technology represented by laser powder bed fusion (LPBF) has been widely used in the manufacture of Inconel 718 high-temperature alloy due to its advantages of not being restricted by part geometry and having a short production cycle. However, although the static load mechanical properties of Inconel 718 high-temperature alloy formed by LPBF process are comparable to or even exceed those of traditional forgings, its creep performance is still significantly lower than that of forgings.
[0004] The root cause of this performance difference lies in the unique microstructural characteristics of the LPBF-formed alloy, including irregular grain morphology and uneven grain size. These characteristics lead to stress concentration at the grain boundaries, significantly increasing the number and expansion rate of grain boundary cracks, and limiting the creep performance of the material. Therefore, for the LPBF-formed Inconel 718 high-temperature alloy with unique microstructural characteristics, it is urgent to find an effective way to strengthen the grain boundaries to improve its creep performance. Summary of the invention
[0005] The present disclosure proposes a heat treatment method for improving the creep performance of LPBF nickel-based high-temperature alloy and the nickel-based high-temperature alloy obtained thereby, so as to solve the technical problem that the conventional heat treatment process is applied to the LPBF formed nickel-based high-temperature alloy, resulting in the reduction of its creep performance.
[0006] In a first aspect, the present disclosure provides a heat treatment method for improving the creep properties of an LPBF nickel-based high-temperature alloy, comprising: performing a homogenization heat treatment on the nickel-based high-temperature alloy after LPBF forming, comprising a first heat preservation and a first water cooling after the first heat preservation; performing a solution treatment on the nickel-based high-temperature alloy after the homogenization heat treatment, comprising a second heat preservation, cooling to different solid solution temperatures at a first cooling rate after the second heat preservation, and then performing a second water cooling; and performing a two-stage aging heat treatment on the nickel-based high-temperature alloy after the solid solution treatment to obtain a target nickel-based high-temperature alloy.
[0007] According to a preferred embodiment of the first aspect, the homogenization heat treatment further comprises performing the first water cooling after the first heat preservation at a temperature of 1080° C. to 1100° C. for 2 to 3 hours.
[0008] According to a preferred embodiment of the first aspect, the solution treatment further includes performing the second heat preservation at a temperature of 1020°C to 1050°C for 0.5 to 1 h, cooling to different solution temperatures at the first cooling rate, and then performing the second water cooling.
[0009] According to a preferred embodiment of the first aspect, the first cooling rate is 0.01-5°C / min, and the different solid solution temperatures are 800°C-900°C.
[0010] According to a preferred embodiment of the first aspect, the double-stage aging treatment includes a third heat preservation, furnace cooling at a second cooling rate after the third heat preservation, and a fourth heat preservation before taking out and air cooling to room temperature.
[0011] According to a preferred embodiment of the first aspect, the double-stage aging treatment further includes: performing a third insulation at a temperature of 700-720°C for 6-8 hours; after the third insulation, cooling with the furnace to 620-650°C at the second cooling rate of 30-80°C / h and performing the fourth insulation for 6-8 hours, and then taking out and air cooling to room temperature.
[0012] According to a preferred embodiment of the first aspect, before the two-stage aging heat treatment, the method further comprises subjecting the nickel-based high-temperature alloy after the solid solution treatment to a fifth heat preservation step at a temperature of 970 to 980° C. for 0.5 to 1 h.
[0013] In a second aspect, the present disclosure provides a nickel-based high-temperature alloy prepared by the heat treatment method according to any one of the first aspects.
[0014] According to a preferred embodiment of the second aspect, the nickel-based high-temperature alloy has one or more of the following characteristics: δ phase is distributed at the grain boundaries, the grain boundaries between grains include serrated grain boundaries, the average amplitude of the serrated grain boundaries is greater than 1 μm, and the average wavelength is greater than 1.2 μm.
[0015] According to a preferred embodiment of the second aspect, the nickel-based high-temperature alloy has one or more of the following mechanical properties: yield strength not less than 1154 MPa, tensile strength not less than 1387 MPa, and elongation not less than 22%.
[0016] The main beneficial effect of the present disclosure is that, for LPBF-formed nickel-based high-temperature alloys, by changing the intermediate solid solution temperature and controlling the cooling rate, a serrated grain boundary is introduced, which has the characteristics of simple process and easy implementation. In addition, the LPBF-formed nickel-based high-temperature alloy obtained by the heat treatment method of the present disclosure will not damage its room temperature mechanical properties, and the high-temperature creep performance is also greatly improved, which broadens the application range of LPBF-formed nickel-based high-temperature alloys.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate one or more embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure and to enable one of ordinary skill in the relevant art to make and use the present disclosure.
[0019] Figure 1 It is a schematic flow diagram of a heat treatment method according to an embodiment of the present disclosure.
[0020] Figure 2 FIG. 1 is a schematic diagram of the cross-sectional structure of an LPBF-formed Inconel 718 high-temperature alloy according to an embodiment of the present disclosure.
[0021] Figure 3 Schematic diagram of the longitudinal cross-section structure of the LPBF-formed Inconel 718 high-temperature alloy according to an embodiment of the present disclosure.
[0022] Figure 4 2 are grain boundary diagrams of LPBF-formed Inconel 718 high-temperature alloy under different heat treatment mechanisms according to an embodiment of the present disclosure, wherein (a) is HT-1 of Comparative Example 1, (b) is HT-2 of Example 1, and (c) is HT-3 of Example 2.
[0023] Figure 5 1 is a serrated grain boundary diagram of the LPBF-formed Inconel 718 high-temperature alloy produced under slow cooling and grain bending heat treatment according to an embodiment of the present disclosure, wherein (a) is HT-2 of Example 1, and (b) is HT-3 of Example 2.
[0024] Figure 6 It is a processing diagram of the serrated grain boundary of Inconel 718 high-temperature alloy formed by LPBF according to an embodiment of the present disclosure.
[0025] Figure 7It is a bar chart of room temperature tensile properties of LPBF-formed Inconel 718 high-temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Examples 1-2) according to an embodiment of the present disclosure, including yield strength, tensile strength, and elongation.
[0026] Figure 8 It is a time displacement curve of a small punch creep experiment of LPBF-formed Inconel 718 high-temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Example 2) according to an embodiment of the present disclosure.
[0027] Fig. 9 It is the equivalent stress-strain curve of the small punch creep experiment of the LPBF-formed Inconel 718 high-temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Example 2) according to the embodiment of the present disclosure.
[0028] Fig.10 These are EBSD images near the creep fracture and geometric necessary dislocation density (GND) statistical diagrams according to the embodiments of the present disclosure, wherein (a), (b), and (c) are comparative example 1, and (d), (e), and (f) are example 2. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments may be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; rather, the description of these embodiments is intended to make the present disclosure more comprehensive and complete and to fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a deeper understanding of the embodiments of the present disclosure.
[0030] It should be understood that the "LPBF" mentioned in the present disclosure is the Laser Powder Bed Fusion technology, which uses a method of adding powder materials layer by layer, and gradually melts and solidifies each layer of powder by precisely controlling the heat of the laser beam to finally form a three-dimensional component. LPBF can achieve a high-precision forming process based on a digital model generated by computer-aided design (CAD) software, thereby obtaining high-quality nickel-based high-temperature alloy components.
[0031] <Overview of Implementation Method>
[0032] The present disclosure generally relates to heat treating a nickel-based superalloy formed by LPBF to obtain a nickel-based superalloy with significantly improved creep performance. Figure 1 Schematic diagram of the heat treatment method according to the embodiment of the present disclosure. Figure 1As shown, the overall implementation of the heat treatment method 10 is shown below.
[0033] 11. Homogenization heat treatment
[0034] The heat treatment method 10 disclosed in the present invention has the step of performing a homogenization heat treatment 11 on the nickel-based high-temperature alloy formed by LPBF. The homogenization heat treatment 11 includes performing a first heat preservation treatment on the nickel-based high-temperature alloy and performing a first water cooling treatment on the nickel-based high-temperature alloy after the first heat preservation. Further, the homogenization heat treatment 11 includes performing a first heat preservation treatment on the nickel-based high-temperature alloy at a temperature of 1080°C to 1100°C for 2 to 3 hours and then performing a first water cooling treatment.
[0035] 12. Solution treatment
[0036] The heat treatment method 10 disclosed in the present invention has the step of performing a solution treatment 12 on the nickel-based high-temperature alloy after the homogenization heat treatment 11. The solution treatment 12 includes performing a second heat preservation treatment on the nickel-based high-temperature alloy, and cooling the nickel-based high-temperature alloy to different solid solution temperatures at a first cooling rate after the second heat preservation, and then performing a second water cooling treatment. Further, the solution treatment 12 includes performing a second heat preservation of the nickel-based high-temperature alloy at a temperature of 1020°C to 1050°C for 0.5 to 1h, cooling the nickel-based high-temperature alloy to different solid solution temperatures at a first cooling rate, and then performing a second water cooling. Further, the solution treatment 12 includes performing a second heat preservation of the nickel-based high-temperature alloy at a temperature of 1020°C to 1050°C for 0.5 to 1h, cooling the nickel-based high-temperature alloy to different solid solution temperatures at a first cooling rate of 0.01 to 5°C / min, and then performing a second water cooling.
[0037] 13. Double-stage aging heat treatment
[0038] The heat treatment method 10 disclosed in the present invention has the step of performing a double-stage aging heat treatment 13 on the nickel-based high-temperature alloy after the solid solution treatment 12 to obtain the target nickel-based high-temperature alloy. The double-stage aging heat treatment 13 is divided into a first aging treatment 131 and a second aging treatment 132. The first aging treatment 131 includes performing a third heat preservation treatment on the nickel-based high-temperature alloy, and the second aging treatment 132 includes cooling with the furnace at a second cooling rate after the third heat preservation and performing a fourth heat preservation treatment, and then taking it out and air cooling it to room temperature. Further, the first aging treatment 131 includes performing a third heat preservation of the nickel-based high-temperature alloy at a temperature of 700 to 720°C for 6 to 8 hours, and the second aging treatment 132 includes cooling with the furnace to 620 to 650°C at a second cooling rate of 30 to 80°C / h after the third heat preservation and performing a fourth heat preservation for 6 to 8 hours, and then taking it out and air cooling it to room temperature.
[0039] In some embodiments, before the double-stage aging heat treatment 13, the heat treatment method 10 of the present disclosure further has a treatment step of performing a fifth heat preservation on the solution-treated nickel-based superalloy at a temperature of 970-980 °C for 0.5-1 h.
[0040] It should be understood that the nickel-based superalloys involved in the present disclosure have various models, and these alloys are widely used in engineering applications under high-temperature environments. In addition to Inconel 718 mentioned above, the present disclosure also covers various other common types of nickel-based superalloys, including but not limited to Alloy 713 (K418), Alloy 738, Inconel 625, Hastelloy X, etc.
[0041] Hereinafter, taking Inconel 718 superalloy as an example, the specific applications of the embodiments of the present disclosure will be described in detail.
[0042] <Embodiments of Inconel 718 Superalloy>
[0043] The process parameters of LPBF forming Inconel 718 superalloy play an important role in the final formed microstructure and mechanical properties, and can be set according to actual requirements. For example, in an embodiment of the present disclosure, the preferred process parameters for LPBF forming Inconel 718 superalloy are set as laser power 200 W, scanning speed 900 mm / s, spot diameter 70 μm, layer thickness 30 μm, hatch spacing 90 μm, and interlayer rotation 67°. By setting the above parameters, the heat conduction, the morphology of the molten pool and its cooling rate during the forming process can be optimized, so as to obtain an ideal microstructure.
[0044] Since the LPBF forming technology is significantly different from traditional manufacturing processes such as casting or forging, there are also significant differences in the microstructure characteristics of LPBF formed Inconel 718 superalloy. For example, refer to Figure 2 and Figure 3 , which are respectively schematic diagrams of the cross-sectional and longitudinal-sectional microstructures of LPBF formed Inconel 718 superalloy according to the embodiments of the present disclosure. Traditional manufacturing processes usually achieve the crystallization and precipitation of strengthening phases of alloys through slower cooling rates and longer treatment times to form a uniform microstructure with good properties. In the LPBF forming process, however, the metal powder is rapidly cooled after being melted layer by layer by the laser, resulting in unique characteristics in the microstructure of the rapidly solidified alloy.
[0045] Comparative Example 1
[0046] A heat treatment method for Inconel 718 superalloy is provided, and the specific implementation process of this method is shown below.
[0047] 11. Homogenization heat treatment: The Inconel 718 high-temperature alloy sample formed by LPBF is first kept at 1100°C for 2h, and then first water-cooled.
[0048] 12. Solution treatment (conventional treatment): The sample after homogenization heat treatment is subjected to a second heat preservation at 980°C for 1 hour, and then a second water cooling is performed.
[0049] 13. Two-stage aging heat treatment: The sample after solution treatment was subjected to a third insulation treatment at 720°C for 8 hours, then furnace cooled to 620°C at a second cooling rate of 50°C / h, and subjected to a fourth insulation treatment for 8 hours. After being taken out, it was air-cooled to room temperature to obtain sample HT-1.
[0050] Example 1
[0051] A heat treatment method for Inconel 718 high temperature alloy is provided, and the specific implementation process of the method is shown below.
[0052] 11. Homogenization heat treatment: The Inconel 718 high-temperature alloy sample formed by LPBF is first kept at 1100°C for 2h, and then first water-cooled.
[0053] 12. Solution treatment (slow cooling and grain bending heat treatment): The sample after homogenization heat treatment is kept at 1020°C for 0.5h for the second time, then cooled to 860°C at a first cooling rate of 0.4°C / min, and then water cooled for the second time.
[0054] 12.1. After the slow cooling and grain bending heat treatment, since the first cooling rate and the solution termination temperature are relatively low, there are relatively large strengthening phases inside the grains. Therefore, the sample after the solution treatment is subjected to the fifth insulation at 980°C for 1 hour to dissolve the relatively large strengthening phases, and then water-cooled.
[0055] 13. Two-stage aging heat treatment: The sample treated in step 12.1 was subjected to a third insulation treatment at 720°C for 8 hours, then furnace cooled to 620°C at a second cooling rate of 50°C / h, and subjected to a fourth insulation treatment for 8 hours. After being taken out, it was air-cooled to room temperature to obtain sample HT-2.
[0056] Example 2
[0057] A heat treatment method for Inconel 718 high temperature alloy is provided, and the specific implementation process of the method is shown below.
[0058] 11. Homogenization heat treatment: The Inconel 718 high-temperature alloy sample formed by LPBF is first kept at 1100°C for 2h, and then first water-cooled.
[0059] 12. Solution treatment (slow cooling and grain bending heat treatment): The sample after homogenization heat treatment is kept at 1020°C for 0.5h for the second time, then cooled to 840°C at a first cooling rate of 0.2°C / min, and then water-cooled for the second time.
[0060] 12.1. After the slow cooling and grain bending heat treatment, the difference from Example 1 is that the first cooling rate and the termination solid solution temperature are different, and the wavelength and amplitude of the generated serrated grain boundary will be different. Since the first cooling rate is low and the solid solution termination temperature is low, there are also large-sized strengthening phases inside the grains at this time, so the sample after the solid solution treatment is subjected to the fifth heat preservation at a temperature of 980°C for 1h to dissolve the large-sized strengthening phases, and then water-cooled after dissolution.
[0061] 13. Two-stage aging heat treatment: The sample treated in step 12.1 was subjected to a third insulation treatment at 720°C for 8 hours, then furnace cooled to 620°C at a second cooling rate of 50°C / h, and subjected to a fourth insulation treatment for 8 hours. After being taken out, it was air-cooled to room temperature to obtain sample HT-3.
[0062] Microstructure characterization
[0063] Figure 4 2 are grain boundary diagrams of LPBF-formed Inconel 718 high-temperature alloy under different heat treatment mechanisms according to an embodiment of the present disclosure, wherein (a) is HT-1 of Comparative Example 1, (b) is HT-2 of Example 1, and (c) is HT-3 of Example 2.
[0064] Figure 5 1 is a serrated grain boundary diagram of the LPBF-formed Inconel 718 high-temperature alloy produced under slow cooling and grain bending heat treatment according to an embodiment of the present disclosure, wherein (a) is HT-2 of Example 1, and (b) is HT-3 of Example 2.
[0065] according to Figure 4 (a), the microstructure of HT-1 shows straight grain boundary characteristics. Straight grain boundaries are a type of grain boundary morphology that is easily formed under conventional heat treatment conditions. The formation of this type of grain boundary is mainly affected by the solution treatment temperature and cooling rate. Specifically, during the solution treatment (conventional treatment) stage, the temperature is directly reduced to room temperature at a faster cooling rate. Due to the lack of thermodynamic and kinetic conditions during the slow cooling process, the migration and bending of the grain boundaries are limited, resulting in the formation of a straight grain boundary morphology. In addition, Figure 3(a) shows that there are only a small number of small δ-phase particles on the grain boundaries, indicating that the precipitation and aggregation of δ-phase are not significant during the solution treatment process. The microstructural characteristics of the straight grain boundaries have certain limitations on the high-temperature durability of the material.
[0066] according to Figure 4 (b) and Figure 5 (a), the microstructure of HT-2 contains obvious serrated grain boundary characteristics. The serrated grain boundaries are achieved through a slow cooling and bending grain heat treatment process, with an average amplitude of 1.29μm and an average wavelength of 5.15μm. This shows that the treatment conditions of a slow cooling rate of 0.4℃ / min and a solution termination temperature of 860℃ provide a good thermodynamic and kinetic environment for the bending of grain boundaries and the formation of serrated morphology. The serrated grain boundaries are mainly caused by the migration and bending of grain boundaries during the slow cooling process. By regulating the cooling rate and the solution termination temperature, the grain boundaries are affected by stress and thermodynamic driving forces during migration, forming a regular serrated morphology. The appearance of serrated grain boundaries can effectively inhibit grain boundary sliding and enhance the durability of materials in high temperature environments.
[0067] according to Figure 4 (c) and Figure 5 (b), the microstructure of HT-3 also contains serrated grain boundaries, but compared with HT-2, the morphology of the grain boundaries is more obvious and regular. Specifically, the average amplitude increases to 1.75μm, and the average wavelength increases to 6.09μm. It shows that during the heat treatment process of Example 2, by further reducing the cooling rate (0.2℃ / min) and adjusting the solution termination temperature (840℃), the migration and bending of the grain boundaries are more sufficient. The lower cooling rate allows the grain boundaries to have a longer time to migrate and adjust their morphology during the cooling process to form a serrated morphology with a larger amplitude and a longer wavelength. The larger amplitude and wavelength not only improve the serrated morphology of the grain boundaries, but also further enhance the inhibitory effect of the grain boundaries on slip and crack propagation, thereby significantly enhancing the high-temperature mechanical properties of the material. Compared with HT-2, HT-3 has a more significant improvement in high-temperature creep resistance.
[0068] The overall idea of the present disclosure is to introduce serrated grain boundaries in the LPBF-formed Inconel 718 high-temperature alloy through a slow cooling and grain bending heat treatment process, and to transform the straight grain boundaries into serrated grain boundaries by a slow cooling process, thereby realizing the serration of the grain boundaries of the LPBF-formed Inconel 718 high-temperature alloy, and the average amplitude and wavelength of the generated serrated grain boundaries are both greater than 1 μm.
[0069] Specifically, the Inconel 718 high-temperature alloy is first heated to a high temperature of 1080℃~1100℃ and maintained in the first insulation state for 2~3h. The main purpose of this process is to completely dissolve the Laves phase generated by rapid solidification during the forming process, while eliminating residual stress and achieving complete recrystallization of the grains inside the material. Rapid water cooling is performed immediately after the first insulation to ensure that the internal structure of the crystal is effectively controlled and to avoid unnecessary grain boundary precipitation.
[0070] Next, the Inconel 718 high-temperature alloy is heated again to 1020℃~1050℃ for the second heat preservation, and the time is 0.5~1h to ensure that the δ phase can be controlled to precipitate at the grain boundary during the subsequent cooling process. Subsequently, by adjusting the cooling rate, the temperature is slowly cooled to the preset solution termination temperature (800℃~900℃) at the first cooling rate, and then the second water cooling is carried out. This slow cooling process is the core of the whole process. By controlling the cooling rate and the termination solution temperature, serrated grain boundaries can be formed at the grain boundaries. This is because the δ phase precipitated during the slow cooling process will grow in a controlled manner on the grain boundary and interact with the grain boundary migration, thereby producing periodic fluctuations and making the grain boundary present a serrated morphology. The formation of serrated grain boundaries not only depends on the precipitation behavior of the δ phase, but is also closely related to the reasonable matching of the cooling rate and the solution termination temperature. The microstructural evolution at this stage significantly improves the creep resistance of the alloy. However, during the slow cooling process, due to the low cooling rate and low solution termination temperature, a larger γ" strengthening phase may precipitate inside the grains, which will have an adverse effect on the overall mechanical properties of the alloy. In order to eliminate this potential problem, after the slow cooling is completed, the material needs to be heated to 970℃~980℃ again and kept for 0.5~1h (fifth holding) time to completely dissolve the larger γ" phase inside the grains, while the δ phase in the serrated grain boundaries remains basically unchanged.
[0071] Finally, the Inconel 718 high-temperature alloy enters the double-stage aging heat treatment stage, where the material is kept at a temperature of 700-720°C for 6-8 hours for the third time, then cooled to 620-650°C with a second cooling rate of 30-80°C / h and kept for 6-8 hours for the fourth time, and then taken out and air-cooled to room temperature. The main purpose of the double-stage aging is to form a small and evenly distributed γ” strengthening phase inside the grains while maintaining the integrity of the serrated grain boundaries.
[0072] Figure 6 This is a processing diagram of the serrated grain boundary of Inconel 718 high-temperature alloy formed by LPBF according to the embodiment of the present disclosure. Figure 6It can be seen that the cooling rate has a significant effect on the formation of serrated grain boundaries. When the cooling rate is low (such as 0.01℃ / min~0.5℃ / min), the grain boundaries are more inclined to form a serrated shape and enter the "serrated grain boundary" region. This is because the lower cooling rate provides sufficient time for grain boundary migration and promotes the growth of the serrated morphology. As the cooling rate increases (such as 1℃ / min~2℃ / min), the grain boundaries gradually tend to be straightened, it is difficult to form a serrated morphology, and finally enter the "non-serrated grain boundary" region. In addition, from Figure 6 It can be found that by controlling the cooling rate, the micromorphology of the Inconel718 high-temperature alloy grain boundary can be adjusted to meet specific performance requirements. In particular, when the cooling rate ranges from 0.01℃ / min to 0.5℃ / min, the serrated grain boundary formation effect is best, while when the cooling rate exceeds 1℃ / min, the formation of the serrated grain boundary is significantly limited. This shows that the cooling rate is one of the important parameters affecting the formation of the serrated grain boundary of Inconel 718 formed by LPBF.
[0073] Mechanical properties test
[0074] Figure 7 The room temperature tensile properties of the LPBF formed Inconel 718 high temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Examples 1-2) according to the embodiment of the present disclosure are bar graphs, including yield strength, tensile strength, and elongation. The Inconel 718 high temperature alloy in Comparative Example 1 and Examples 1-2 were processed into dog-bone tensile specimens, and mechanical properties were tested in accordance with GB / T228.1 "Metallic Materials Tensile Test Part 1 Room Temperature Test Method", and the data in Table 1 and Figure 7 The bar graph is shown.
[0075]
[0076] Table 1: Room temperature tensile properties of different examples
[0077] Combining Table 1 and Figure 7It can be seen that the LPBF formed Inconel 718 high temperature alloy disclosed in the present invention after slow cold bending heat treatment, the straight grain boundary is transformed into a serrated grain boundary, the amplitude is more than 1μm, and the basic room temperature mechanical properties are not damaged while introducing the serrated grain boundary. Its yield strength is not less than 1154MPa, the tensile strength is not less than 1387MPa, and the elongation is not less than 22%. This organizational transformation significantly improves the ductility of the nickel-based high temperature alloy at room temperature, while maintaining a high performance level in terms of yield strength and tensile strength. It is worth noting that the yield strengths of Example 1 and Example 2 are 1167MPa and 1154MPa, respectively, both exceeding the basic requirements of Inconel 718 high temperature alloy in industrial applications, while the tensile strengths are 1387MPa and 1402MPa, respectively, which also show extremely high reliability. More importantly, the elongation reaches 24% and 22%, respectively, compared with 19% of Comparative Example 1, which significantly improves the toughness and crack resistance of the material. The test results fully demonstrate that the slow cooling and bending heat treatment process can not only introduce serrated grain boundaries and improve the structural stability of the alloy, but also optimize the mechanical properties to a certain extent, especially the significant improvement of elongation, which is of great significance for the application of Inconel 718 high-temperature alloy in complex stress environments. In summary, the heat treatment method disclosed in the present invention ensures the excellence of basic mechanical properties while achieving microstructural regulation, laying a solid foundation for the further engineering application of LPBF-formed Inconel 718 high-temperature alloy.
[0078] Creep test
[0079] Figure 8 It is a time displacement curve of a small punch creep experiment of LPBF-formed Inconel 718 high-temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Example 2) according to an embodiment of the present disclosure. Fig. 9 It is the equivalent stress-strain curve of the small punch creep experiment of the LPBF-formed Inconel 718 high-temperature alloy after conventional heat treatment (Comparative Example 1) and slow cooling heat treatment (Example 2) according to the embodiment of the present disclosure.
[0080] According to the embodiments of the present disclosure, in order to explore the contribution of serrated grain boundaries to creep performance, a detailed small punching creep test was carried out. The test compared the creep performance of two samples, Comparative Example 1, which underwent conventional heat treatment, and Example 2, which adopted slow cooling and heat treatment. The small punching creep test has the characteristics of small equipment volume, small sample requirement, and fast experimental speed. Therefore, it was selected to evaluate the creep performance of LPBF formed Inconel 718 high temperature alloy. This experiment was carried out in strict accordance with the standard of BS EN10371-2021 "Methods for Small Punching of Metallic Materials Part 8 Small Punching Creep Test". The test equipment includes an upper die seat, a lower die seat, a push rod and a punch ball with a size of 2.5 mm. The specimen is a disc with a diameter of 9.8 mm and a thickness of 0.5 mm. The dimensional accuracy is 0.001 mm, and the test conditions are 650°C / 750N.
[0081] The output result of the small punching creep test is a time displacement curve, where time is the creep life. The equivalent stress-strain curve is obtained based on the time displacement curve, and the equivalent creep strain rate can be obtained by differentiating the equivalent stress-strain curve. The results of Comparative Example 1 and Example 2 are shown in Tables 2 and Figure 8-Figure 9 As shown in the curve graph.
[0082]
[0083] Table 2: Creep properties of different examples
[0084] The above data show that the difference between Example 2 and Comparative Example 1 is that the microstructure of Example 2 contains serrated grain boundaries, and other conditions are the same. At this time, compared with Comparative Example 1, the creep life of Example 2 is increased by 56%, the creep strain is increased by 19%, and the creep strain rate is reduced by 26%. This fully demonstrates that the slow cooling and heat treatment process has a significant effect on improving the creep performance by introducing serrated grain boundaries.
[0085] Fig.10 EBSD images and geometric necessary dislocation density (GND) statistics near the creep fracture according to the embodiment of the present disclosure, wherein (a), (b), and (c) are comparative example 1, and (d), (e), and (f) are example 2. Fig.10 It can be seen that the stress concentration near the straight grain boundary in Comparative Example 1 is more obvious, and after the crack initiates at the grain boundary, it is easy to propagate along the grain boundary. The presence of the serrated grain boundary in Example 2 significantly reduces the stress concentration near the grain boundary and slows down the initiation of cracks near the grain boundary. After the crack initiates, the propagation of the crack is hindered due to the large amplitude of the serrated grain boundary, which further slows down the failure of the material and prolongs the service life of the material. Compared with hindering the crack propagation, the presence of the serrated grain boundary plays a more critical role in delaying the initiation of cracks.
[0086] From the above results, it can be seen that the slow cooling heat treatment process disclosed in the present invention adopts an appropriate solution temperature and a relatively slow cooling rate, and the grain boundaries are serrated through the interaction of grain boundary migration and grain boundary precipitation phase (mainly δ phase). The introduction of serrated grain boundaries not only optimizes the microstructure of LPBF-formed Inconel 718 high-temperature alloy, but also effectively improves its high-temperature creep resistance, while ensuring that the room temperature mechanical properties are not affected. Specifically, the slow cooling process leads to the formation of a serrated structure during grain boundary migration. This structure significantly improves the ability of grain boundaries to hinder crack propagation, and the precipitation of δ phase at the grain boundaries further enhances the creep resistance of the material. Compared with conventional heat treatment processes, slow cooling heat treatment can greatly improve the elongation, high-temperature creep life and crack resistance without affecting the yield strength and tensile strength.
[0087] Through the slow cooling heat treatment process disclosed in the present invention, the creep resistance of LPBF-formed Inconel 718 high-temperature alloy in a high-temperature environment is significantly improved, which extends the service life of the material and enables it to be more widely used in aerospace, nuclear energy and other fields requiring high temperature and high stress tolerance.
[0088] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. The present disclosure is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof.
Claims
1. A heat treatment method for improving the creep performance of LPBF nickel-based high-temperature alloy, comprising: Performing a homogenization heat treatment on the nickel-based high-temperature alloy formed by LPBF, including a first heat preservation and a first water cooling after the first heat preservation; The nickel-based high-temperature alloy after the homogenization heat treatment is subjected to a solid solution treatment including a second heat preservation, cooling to different solid solution temperatures at a first cooling rate after the second heat preservation, and then a second water cooling; as well as The nickel-based high-temperature alloy after the solid solution treatment is subjected to a double-stage aging heat treatment to obtain a target nickel-based high-temperature alloy.
2. The heat treatment method according to claim 1, wherein: The homogenization heat treatment further includes performing the first water cooling after the first heat preservation at a temperature of 1080° C. to 1100° C. for 2 to 3 hours.
3. The heat treatment method according to claim 1, wherein: The solution treatment further includes performing the second heat preservation at a temperature of 1020° C. to 1050° C. for 0.5 to 1 h, cooling at the first cooling rate to different solution temperatures, and then performing the second water cooling.
4. The heat treatment method according to claim 3, wherein: The first cooling rate is 0.01-5°C / min, and the different solid solution temperatures are 800°C-900°C.
5. The heat treatment method according to claim 1, wherein: The double-stage aging treatment comprises a third heat preservation, furnace cooling at a second cooling rate after the third heat preservation, a fourth heat preservation, and then air cooling to room temperature.
6. The heat treatment method according to claim 5, wherein: The double-stage aging treatment further comprises: - The third insulation is carried out at a temperature of 700-720°C for 6-8h; - After the third heat preservation, the furnace is cooled to 620-650° C. at the second cooling rate of 30-80° C. / h and the fourth heat preservation is performed for 6-8 hours, and then taken out and air-cooled to room temperature.
7. The heat treatment method according to claim 1, 3 or 4, wherein: Before the two-stage aging heat treatment, the method further comprises performing a fifth heat preservation step at a temperature of 970 to 980° C. for 0.5 to 1 h on the nickel-based high-temperature alloy after the solid solution treatment.
8. A nickel-based high-temperature alloy prepared by the heat treatment method according to any one of claims 1 to 7.
9. The nickel-based high-temperature alloy according to claim 8, having one or more of the following features: The δ phase is distributed at the grain boundaries, the grain boundaries between the grains include serrated grain boundaries, the average amplitude of the serrated grain boundaries is greater than 1 μm, and the average wavelength is greater than 1.2 μm.
10. The nickel-based high-temperature alloy according to claim 8, having one or more of the following mechanical properties: The yield strength shall not be less than 1154Mpa, the tensile strength shall not be less than 1387Mpa, and the elongation shall not be less than 22%.